EFFECTS OF Sr SUBSTITUTION ON CRYSTALLINE STRUCTURE AND RAMAN SPECTRA OF La2-xSrxNiO4+? - Tran Dang Thanh; Le Van Hong (ASEAN Journal on Science and Technology for Development, 2008)
Effects of Sr2+ substitution for La3+  on oxygen concentration and structure of La2-xSrxNiO4+?   have been observed by X-ray diffraction and Raman scattering. Oxygen concentration and unit cell volume of the material decrease monotonously in dependence of x.   The vibration modes were calculated for La2NiO4 in K2NiF4  type structure with the group symmetry of I4/mmm. The Raman active modes for this symmetry were also theoretically identified. Raman back scattering spectra have been carried out for all the ceramic polycrystalline samples at room temperature. Two Raman lines at 224.6 cm-1  and 433 cm-1 , assigned to Eg  and A1g  vibration modes of oxygen O(II) in bonding La/Sr-O were observed for all the samples. The lower mode 224.6 cm-1  shifts down to 208 cm-1 , whereas the upper mode 433 cm-1  shifts up when concentration of the Sr substituting for La increases.